(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The partition of India in 1947 stands as one of the most significant and tragic events in modern history. It resulted in the division of British India into two sovereign states, India and Pakistan, and led to widespread violence, mass migrations, and long-lasting social, political, and cultural impacts. This paper explores the key causes behind the partition, including the colonial policies, religious and political tensions, and the role of key leaders. It also examines the immediate and long-term consequences of the partition, which include the creation of religiously based national identities, demographic shifts, and the enduring legacy of communal tensions. Finally, the paper offers insights into the historical significance of the partition and reflects on its continued influence on the geopolitical landscape of South Asia.